Participation and performance at the London 2012 Olympics - Kuper, G. H.; Sterken, E. (Research Institute SOM, Faculty of Economics & Business, University of Groningen, 2012)
The current paper predicts the medal tally for the London 2012 Olympic Games. The forecast procedure consists of analyzing participation and success at the country level of the three most recent editions of the Olympic Summer Games. Potential explanatory variables for medal winnings are income per capita, population, geographical distance to the Games, success in terms of medals won at World Championships, and the home advantage. Our forecasts show that the China takes first place in the medal tally with 44 gold medals, followed by the United States of America winning 33 gold medals. We expect Great Britain to take fourth place winning 23 gold medals.